2017
DOI: 10.3390/toxins9090277
|View full text |Cite
|
Sign up to set email alerts
|

Bordetella Adenylate Cyclase-Hemolysin Toxins

Abstract: Adenylate cyclase-hemolysin toxin is secreted and produced by three classical species of the genus Bordetella: Bordetella pertussis, B. parapertussis and B. bronchiseptica. This toxin has several properties such as: (i) adenylate cyclase activity, enhanced after interaction with the eukaryotic protein, calmodulin; (ii) a pore-forming activity; (iii) an invasive activity. It plays an important role in the pathogenesis of these Bordetella species responsible for whooping cough in humans or persistent respiratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 89 publications
1
30
0
Order By: Relevance
“…Five well-characterised virulence genes that thought to be involved in interactions with the host were screened in the isolates, including filamentous haemagglutinin (FHA) ( fhaB), pertactin ( prn), adenylate cyclase-haemolysin toxin (cyaA), dermonecrotic toxin (dnt) and the Bordetella type-III secretion system effector A (bteA) [15][16][17][18][19]. The primers for amplification of the five virulence genes were designed based on the corresponding genes in the NCBI database (https://www.ncbi.nlm.nih.gov/) ( Table 1).…”
Section: Virulence Gene Detectionmentioning
confidence: 99%
“…Five well-characterised virulence genes that thought to be involved in interactions with the host were screened in the isolates, including filamentous haemagglutinin (FHA) ( fhaB), pertactin ( prn), adenylate cyclase-haemolysin toxin (cyaA), dermonecrotic toxin (dnt) and the Bordetella type-III secretion system effector A (bteA) [15][16][17][18][19]. The primers for amplification of the five virulence genes were designed based on the corresponding genes in the NCBI database (https://www.ncbi.nlm.nih.gov/) ( Table 1).…”
Section: Virulence Gene Detectionmentioning
confidence: 99%
“…It should be aware that the PRN-deficient B. pertussis had emerged, and the losses of the prn gene expression in the strains might be driven by using of acellular vaccine containing PRN [14]. The cyaA gene encodes the multifunctional adenylate cyclasehemolysin (AC-Hly) toxin, which possess adenylate cyclase activity, pore-forming activity and cell invasive activity [15]. It was showed that the AC-Hly toxin expressed in the B. bronchiseptica strains isolated from human and rabbit was responsible for the lethality of the intranasally infected mice [7].…”
Section: Virulence Genes Detectionmentioning
confidence: 99%
“…The adenylate cyclase (CyaA) toxin is a major virulence factor produced by Bordetella pertussis, the causative agent of whooping cough, and is involved in the early stages of respiratory tract colonization [1][2][3][4][5] . CyaA, a 1706-residue long protein ( Figure S1), is a Repeatin-ToXin (RTX) [6][7][8][9][10] multi-domain toxin [11][12] .…”
Section: Introductionmentioning
confidence: 99%